2020
DOI: 10.4252/wjsc.v12.i7.633
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells induce M2 microglia polarization through PDGF-AA/MANF signaling

Abstract: BACKGROUND Bone marrow mesenchymal stem cells (BMSCs) are capable of shifting the microglia/macrophages phenotype from M1 to M2, contributing to BMSCs-induced brain repair. However, the regulatory mechanism of BMSCs on microglia/macrophages after ischemic stroke is unclear. Recent evidence suggests that mesencephalic astrocyte–derived neurotrophic factor (MANF) and platelet-derived growth factor-AA (PDGF-AA)/MANF signaling regulate M1/M2 macrophage polarization. AIM To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Other studies support the idea that the balance between both activated phenotypes could determine the neurodegenerative disease progression, so that a majority of the M1 population is associated with a worse clinical prognosis [ 36 ]. Interestingly, activated microglia are known to switch from one profile to another and a great number of therapies are focused on this property [ 37 , 38 , 39 ]. M1 activated microglia contribute to an increase in the inflammation and cytotoxicity levels through the release of the cytokines TNF-α and IFN-γ; interleukins such as IL-1β, IL-6, IL-15, IL-18, and IL-23; chemokines like CCL2 and CXCL10; the metalloproteinases (MMPs) MMP-3 and MMP-9; and reactive oxygen/nitrogen species (ROS/RNS) [ 40 , 41 ].…”
Section: Microgliamentioning
confidence: 99%
“…Other studies support the idea that the balance between both activated phenotypes could determine the neurodegenerative disease progression, so that a majority of the M1 population is associated with a worse clinical prognosis [ 36 ]. Interestingly, activated microglia are known to switch from one profile to another and a great number of therapies are focused on this property [ 37 , 38 , 39 ]. M1 activated microglia contribute to an increase in the inflammation and cytotoxicity levels through the release of the cytokines TNF-α and IFN-γ; interleukins such as IL-1β, IL-6, IL-15, IL-18, and IL-23; chemokines like CCL2 and CXCL10; the metalloproteinases (MMPs) MMP-3 and MMP-9; and reactive oxygen/nitrogen species (ROS/RNS) [ 40 , 41 ].…”
Section: Microgliamentioning
confidence: 99%
“…However, instead of promoting the re-growth of tissue resident cells, these factors drive tumor growth. Likewise, macrophages also secrete key effectors of vascularization, like the vascular endothelial growth factor (VEGF) (42,43), plateletderived growth factor (PDGF) (44) and transforming growth factor b (TGFb) (45) to promote angiogenesis (Figure 1). These physiologic processes are hijacked to increase blood flow to the tumor, increasing tumor cell access to oxygen and nutrients for continued cell proliferation.…”
Section: The Role Of Macrophages In the Anti-tumor Responsementioning
confidence: 99%
“…Conversely, the presence of M2 pro-wound healing macrophages in tumors is generally a negative prognostic marker, with patients with high numbers of intra-tumoral M2 macrophages showing decreased survival (67). Tumor cells are known to secrete, or induce the secretion of, factors like IL-4, IL-10 or IL-13 that polarize macrophages toward an M2 phenotype (44,68). Some pro-wound healing properties of M2 macrophages foster tumor growth and prepare a tumor-friendly milieu (Figure 1).…”
Section: The Role Of Macrophages In the Anti-tumor Responsementioning
confidence: 99%
“…This research suggested that Ly6C+ cells may consist of heterogeneous populations in the infarct area, which can be modulated by intravenously infused allogeneic MSCs. Meanwhile, that BMSCs inactivated the microglia and induced M2 polarization was further observed by other researchers (Li et al, 2019d;Yang et al, 2020c). Oh et al (2018) demonstrated that human umbilical cord mesenchymal stem cells (hUMSCs) could relieve neuroinflammation in rodent stroke models by increasing interleukin-1 receptor antagonist (IL-1ra) expression in macrophage cell lines.…”
Section: The Immunomodulatory Effect Of Mscs and Neuroinflammationmentioning
confidence: 86%